Efektivitas Kebijakan Perlindungan Data Pribadi di Indonesia: Analisis Hukum Perdata dengan Pendekatan Studi Kasus - Kriswandaru, Althea Serafim; Pratiwi, Berliant; Suwardi, Suwardi (LPPM Universitas Sains dan Teknologi Komputer, 2024)
The protection of personal data has emerged as a critical concern in the digital era, particularly in Indonesia, where data breaches are increasing at an alarming rate. This study investigates the effectiveness of Indonesia's data protection policies, focusing on the implementation of Law No. 27 of 2022, and identifies the factors affecting its enforcement. Employing a qualitative approach with a case study methodology, the research analyzes three major data breach incidents involving Tokopedia, BRI Life, and BPJS Kesehatan. Data collection methods included in-depth interviews with legal practitioners and document analysis of relevant regulations and reports. The findings reveal significant gaps in the enforcement of Law No. 27 of 2022, including weak sanctions, inadequate oversight mechanisms, and limited public awareness of data privacy rights. Although the law provides a foundational framework, its effectiveness is hindered by insufficient penalties and the absence of an independent supervisory authority. For instance, while Tokopedia implemented policy revisions post-breach, similar incidents remain likely due to inadequate deterrent measures. Comparatively, the European Union's General Data Protection Regulation (GDPR) demonstrates higher effectiveness through stringent sanctions and robust enforcement mechanisms. This study contributes to the discourse on data privacy by highlighting the shortcomings of Indonesia’s current policies and proposing strategic recommendations. These include harmonizing domestic regulations with international standards, strengthening enforcement through independent oversight bodies, and enhancing public education on data privacy rights. By addressing these challenges, Indonesia can establish a more robust data protection framework, fostering trust in its digital ecosystem and ensuring alignment with global practices.